The Islamic Corporate Governance Implementation and Program at Miftahussunnah Islamic Boarding School - Muhamad Nafik Hadi Ryandono, Widita Kurniasari, Tjiptohadi Sawarjuwono, (Opción, 2019)
This research designs and implements Islamic Corporate Governance (ICG) at pondok pesantren (Islamic boarding school) Miftachussunnah in Surabaya so that it can be used as a reference for the improvement of governance and institutional structure in the pondok pesantren. This research will use the qualitative method. As a result, the discussions in this financial aspect include three things: financial planning and management conditions, analysis and recommendations. In conclusion, the preparatory phase consists of several steps, namely: a preliminary survey, findings, analysis of findings primarily to analyze governance management and institutional structures.